Putative Risk Factors in Developmental Dyslexia: A Case-Control Study of Italian Children. (March 2015) - Mascheretti, Sara; Marino, Cecilia; Simone, Daniela; Quadrelli, Ermanno; Riva, Valentina; Cellino, Maria Rosaria; Maziade, Michel; Brombin, Chiara; Battaglia, Marco
Although dyslexia runs in families, several putative risk factors that cannot be immediately identified as genetic predict reading disability. Published studies analyzed one or a few risk factors at a time, with relatively inconsistent results. To assess the contribution of several putative risk factors to the development of dyslexia, we conducted a case-control study of 403 Italian children, 155 with dyslexia, by implementing a stepwise logistic regression applied to the entire sample, and then to boys and girls separately. Younger parental age at child's birth, lower parental education, and risk of miscarriage significantly increased the odds of belonging to the dyslexia group (19.5% of the variation). These associations were confirmed in the analyses conducted separately by sex, except for parental education, which significantly affected only males. These findings support reading disabilities as a multifactorial disorder and may bear some importance for the prevention and/or early detection of children at heightened risk for dyslexia.